GENERASI Z DAN IDENTITAS BUDAYA DI INDONESIA: APAKAH GLOBALISASI MENGIKIS KEBERAGAMAN BUDAYA LOKAL? - Afifah Aulia Fitri; Linda Zakiah; Aisyah Nurul Izzah; Marini Trianingsih; Nisrina Ayu Anareta Sanjaya; Rahma Diva Ifadha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is based on concerns about the fading of local cultural identity amongIndonesian Generation Z, caused by the strong current of globalization and theinfluence of foreign culture through digital media. The main objective of this study isto examine Generation Z's response to globalization in the context of local culturalidentity and to explore their potential in preserving culture through the use of digitaltechnology. This study was conducted using a literature study method, namelyreviewing a number of scientific journals that discuss topics around Generation Z,globalization, and local culture. The results of the study show that globalization hasa major impact on the mindset, behavior, and cultural awareness of the youngergeneration. Although there is a decrease in attachment to traditional cultural values,Generation Z also shows high adaptive abilities by utilizing social media to creativelydisplay and disseminate local culture. This study concludes that digital media is adialectical field of cultural identity: on the one hand, it is a path for the spread offoreign culture, but on the other hand, it has great potential as a means of preservingculture if used appropriately. For future research, it is recommended to conduct afield approach both qualitatively and quantitatively in order to obtain a more concretepicture of Generation Z's views and behavior in preserving culture in the midst ofthe global era.